NILAI-NILAI PENDIDIKAN KARAKTER DALAM PERMAINAN TRADISIONAL SUKU SASAK DI DESA BABUSSSALAM GERUNG LOMBOK BARAT - Tika Safitri; Lalu Hamdian Affandi; Moh. Irawan Zain (JURNAL ILMIAH PENDAS: PRIMARY EDUCATION JOURNAL, 2022)
This research aims to describe the educational values of karater contained in the traditional games of the sasak tribe in the village of babussalaam gerung west Lombok. The research approach used is qualitative research with ethnography methods. Data collection techniques use observation, interviews and documentation. Data analysis uses Milles and Huberman Model data analysis. The results showed that there are character education values in traditional engklek games, traditional congklak games, and traditional catfish starch games. In traditional games, the value of character education includes peace- love, faith and piety, love of the environment, love of the homeland, hard work, learners, creative, brave, discipline, cooperation, solidarity, honesty and deliberation. With the highest percentage of appearances, namely independent characters with a percentage of 100%, then religious characters with a percentage of 75% and continued with mutual aid characters with a percentage of 66%. In traditional games congklak integrated character education values include peace, faith and piety, love of the environment, love of the homeland, hard work, learners, creative, brave, discipline, cooperation, family, honesty and deliberation. With the highest percentage of appearances, namely independent characters with a percentage of 100%, then religious characters with a percentage of 75% and continued with mutual aid characters with a percentage of 66%. In traditional games pati lele integrated character education values include peace, faith and devotion, love of the environment, love of the homeland, hard work, learners, creative, discipline, cooperation, solidarity, honesty and deliberation. With the highest percentage of appearances, namely independent characters with a percentage of 80%, then religious characters with a percentage of 75% and continued with mutual aid characters with a percentage of 66%. The three games are very suitable for cultivating independent, religious and mutual cooperation characters in children.